Adverse Drug Reactions, Treatment Adherence, and Treatment Outcomes in Drug-Resistant Tuberculosis Patients: A Single-center, Cross-sectional Study - Nadia Farhanah Syafhan; Galuh Zhafirah Rahmita; Sri Wulandah Fitriani (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2025)
Drug-Resistant Tuberculosis (DRTB) is a significant global health issue due to its rapid transmission and high morbidity. The variety of medications used in DRTB treatment increases the risk of adverse drug reactions (ADRs), which can contribute to patient nonadherence and adversely affect treatment outcomes. This study aimed to describe the occurrence of ADRs, quantify medication adherence rates, and assess treatment outcomes among patients with drugresistant tuberculosis (DRTB). Furthermore, it sought to analyse the associations between ADRs, demographic and clinical variables, medication adherence, and the associations between ADRs and treatment outcomes. Using a cross-sectional design, this study utilized medical records data and the Tuberculosis Information System (SITB) of adult DRTB patients treated at Universitas Indonesia Hospital from April 1, 2022, to February 28, 2023. A total sampling method was employed to select the research participants. Of the 65 patients, 60 (95.24%) experienced ADRs, and the Medication Refill Adherence method indicated an 89.23% adherence rate. Two patients (3.08%) were classified as successful or cured during the data collection period. Chi-square tests revealed no significant relationship between ADRs and medication adherence (p = 0.373) or treatment outcomes (p = 0.120). All demographic and clinical factors (age, gender, comorbidities, treatment combinations, and potential drug interactions) also showed no significant relationships with adherence (p > 0.05). In contrast, treatment combinations showed significant relationships with treatment outcomes (p = 0.013). These findings highlight the importance of medicines optimisation strategies, including proactive ADR management and adherence support, to improve treatment outcomes in DRTB patients.